Duloxetine in addition to self-management for painful temporomandibular disorders: a post hoc responder analysis of a randomized, placebo-controlled clinical trial - Dyna Mara Araújo Oliveira FERREIRA; Flávia Fonseca Carvalho SOARES; Amanda Ayla RAIMUNDINI; Leonardo Rigoldi BONJARDIM; Yuri Martins COSTA; Paulo César Rodrigues CONTI (University of São Paulo, 2024)
Abstract Aim To identify the phenotypic characteristics of individuals with temporomandibular disorders (TMD) who may benefit from adding duloxetine to self-management (SM) strategies. Methodology This was a post hoc exploratory analysis of a randomized, placebo-controlled clinical trial with SM-duloxetine (duloxetine 60 mg/day plus SM strategies for 12 weeks) in adult participants with painful TMD. The primary outcome was the proportion of responders to treatment (individuals with ≥ 30% reduction in pain intensity) in SM-duloxetine and SM-placebo group at week 12. For responder analysis, five phenotyping domains recommended by Initiative on Methods, Measurement, and Pain Assessment in Clinical Trials were assessed: pain, psychological, sleep, quantitative sensory testing, and conditioned pain modulation. Relative risk (RR), 95% confidence intervals (CI), and absolute risk reduction were calculated. Results Among participants treated with SM-duloxetine, severe pain intensity (RR 1.33, 95% CI: 0.56, 3.17), pain disability (RR 1.30, 95% CI: 0.63, 2.67), ≥ 1 painful comorbidity (RR 1.48, 95% CI: 0.57, 3.79), and anxiety symptoms (RR 1.80, 95% CI: 0.75, 4.34) were associated with greater likelihood of response to treatment. Among individuals treated with SM-placebo, only temporal summation of pain was associated with greater likelihood of response to treatment. Conclusion Personalized medicine may be implemented in painful TMD management, and phenotype characteristics related to pain and psychological domains may predict which individuals with painful TMD are more likely to respond to the addition of serotonin and norepinephrine reuptake inhibitors to SM strategies to clinically and significantly reduce pain intensity.